Workpackage 3 - Smart Tourism Tools - Brito e Abreu, F. (1st General Assembly, European Commission RESETTING project, 2022)
This talk was an overview of the work developed in the scope of RESETTING' Workpackage 3 (Smart Tourism Tools) during the 1st semester of 2022.